Effect of Venting Equipment Installation on Oil Production Stability - Weriono, Weriono; Junaidi, Abdul Khair; Indarto, Kabul (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2024)
Electric Submersible Pumps (ESPs) are one of the most prominent artificial lifting methods in the oil and gas industry today. In the operation of Electric Submersible Pumps on wells in the Ko-Pet field, a gas lock may occur when liquid and gas separate in the tubing above an electric submersible pump and inside the pump. This study aims to determine the effect of installing venting equipment on oil well production. Venting equipment was installed in three oil wells: KI090, KI183, and KI495 in the Ko-Pet oil field. From the production data, it was found that the installation of Venting Equipment affected production stability, namely by increasing the fluid that could be pumped by the ESP to the surface facility. The installation of venting equipment increased oil production by 1251 barrels or an increase of 8%. Electrical Submersible Pump performance was more stable because the gas lock problem can be overcome by continuously releasing the casing pressure with venting equipment.